The Impact of microfinance institutions on poverty alleviation - Collin Chikwira; Edson Vengesai; Petronella Mandude (Journal of Risk and Financial Management, 2022)
Microfinancing has been targeted as a tool to address Poverty through the provision of credit to the poor and marginalised economic functions. However, the main objective upon which these institutions are founded is yet to manifest primarily in developing economies. This study examined the role of microfinancing in poverty alleviation by employing a Vector Error Correction Model on quarterly time-series data. The results reveal a significant long-run relationship among the variables poverty, microfinancing, SMEs, and agricultural growth. Contrary to expectations, Microfinancing was found to increase poverty in the long run. SMEs and agricultural development were found to reduce the level of poverty in the long run. In the short run, regression results reveal that SMEs' growth alleviates poverty, and poverty increases the growth of microfinance loans in the country. The increase in SMEs is a tool for alleviating poverty, and the growth in microfinance institutions is also being driven by poverty. This suggests that continued improper microfinancing can escalate the poverty levels to undesired heights. The findings imply that the growth of microfinance loans is not being put to its intended and efficient use. These findings bring to the fore that it is not only the provision of funds that matters.Microfinancing has been targeted as a tool to address Poverty through the provision of credit to the poor and marginalised economic functions. However, the main objective upon which these institutions are founded is yet to manifest primarily in developing economies. This study examined the role of microfinancing in poverty alleviation by employing a Vector Error Correction Model on quarterly time-series data. The results reveal a significant long-run relationship among the variables poverty, microfinancing, SMEs, and agricultural growth. Contrary to expectations, Microfinancing was found to increase poverty in the long run. SMEs and agricultural development were found to reduce the level of poverty in the long run. In the short run, regression results reveal that SMEs' growth alleviates poverty, and poverty increases the growth of microfinance loans in the country. The increase in SMEs is a tool for alleviating poverty, and the growth in microfinance institutions is also being driven by poverty. This suggests that continued improper microfinancing can escalate the poverty levels to undesired heights. The findings imply that the growth of microfinance loans is not being put to its intended and efficient use. These findings bring to the fore that it is not only the provision of funds that matters.Microfinancing has been targeted as a tool to address Poverty through the provision of credit to the poor and marginalised economic functions. However, the main objective upon which these institutions are founded is yet to manifest primarily in developing economies. This study examined the role of microfinancing in poverty alleviation by employing a Vector Error Correction Model on quarterly time-series data. The results reveal a significant long-run relationship among the variables poverty, microfinancing, SMEs, and agricultural growth. Contrary to expectations, Microfinancing was found to increase poverty in the long run. SMEs and agricultural development were found to reduce the level of poverty in the long run. In the short run, regression results reveal that SMEs' growth alleviates poverty, and poverty increases the growth of microfinance loans in the country. The increase in SMEs is a tool for alleviating poverty, and the growth in microfinance institutions is also being driven by poverty. This suggests that continued improper microfinancing can escalate the poverty levels to undesired heights. The findings imply that the growth of microfinance loans is not being put to its intended and efficient use. These findings bring to the fore that it is not only the provision of funds that matters.
Keywords: 650; SME; VECM; micro finance; poverty